Gereja Asia dalam Konteks Perkembangan Teknologi Informasi dan Komunikasi Serta Pandemi Covid-19 - Mahendra, Felix; Stevanus, Adolvus; Jong, Seratinus (Perspektif, 2022)
This study aims to examine the challenges and opportunities of the Asian Church in the context of developments in information and communication technology and the Covid-19 pandemic. This research departs from the awareness of researchers that human life today cannot be separated from the presence of Information and Communication Technology (ICT) as a means to support various daily activities. The high intensity of the use of this facility shows that this technology has occupied a central role in human life. The Catholic Church in Asia today is also faced with this reality. The duties and responsibilities of someone who has received the gift of baptism (sanctify, preach and serve) should be carried out in the use of ICT. This article focuses on the discussion of ICT which is a challenge for the Catholic Church in Asia during a pandemic, apart from other contexts that it is also facing (the encounter of cultures, religions, and marginalized groups). This research uses a descriptive-qualitative research method. Data are collected from Catholic Church documents as primary data and reputable journals as secondary sources. This research found that fake news (hoaxes) hate speech and narcissistic tendencies are the main challenges in the use of ICT today. However, ICT provides many opportunities for the Catholic Church in Asia to voice the Good News with preaching, sanctification, and service through existing media.